Without actors, there is no action: How interpersonal interactions help to explain routine dynamics - Anja Danner-Schröder (Review of Managerial Science, 2020)
In this paper, we argue that it is important to gain a better understanding on how people interact with each other to explain routine dynamics. Thus, we propose to focus on the interpersonal interactions of actors which is not only the fact that actors interact with each other but that the manner and quality of these interactions is important to understand routine dynamics. By drawing on social exchange theory, we propose a framework that seeks to explain routine dynamics based on different relationships between actors. Building on this framework, we provide different process models indicating how routine performing and patterning is enacted due to the respective relationship of actors. Our insights contribute to research on routine dynamics by arguing (1) that actions of patterning are dependent on the relationship of actors; (2) that trust works as an enabler for creating new patterns of actions; (3) that distrust functions as an enhancer for interrupting and dissolving patterns of actions.
Keywords: M10; 650; Change; Interpersonal interactions; Interpersonal trust; Power asymmetries; Routine dynamics; Routine creation; Social exchange processes